Sistem Tanda Pembukaan Catur Dalam Novel The Queen’s Gambit Karya Walter Tevis - Gencay, Sanda Maulida (PT. Alahyan Publisher Sukabumi, 2023)
This research discusses the chess opening sign system in the novel The Queen’s Gambit by Walter Tevis. The main signifier is the chess opening, the signified of which is strategy and defense in facing and anticipating the opponent's attack to win. The other sign elements in chess opening are The Queen’s Gambit and Sicilian Defense. The signifier is The Queen’s Gambit and the signified is a chess opening strategy by moving the pawn in front of the king to the fourth square to be temporarily sacrificed so that the queen can move at the start of the game. Next is the Sicilian Defense as a signifier. The signified of the Sicilian Defense is an aggressive chess opening where white attacks on the wing of the black king of pieces and black will counterattack on the white minister's wing. The characteristic of the signification is arbitrary where there is no natural relationship between the formal form of the signifier and the concept of the meaning of the signified.